Implementasi Pembelajaran Berbasis Kurikulum Merdeka pada Peserta Didik Kelas 4 Sekolah Dasar Negeri No 16 Pontianak Utara - Warsidah, Warsidah; Satyahadewi, Neva; Amir, Amriani; Linda, Riza; Mulya Ashari, Asri (AR-RIAYAH: Jurnal Pendidikan Dasar, 2022)
Driving school was born from an education system that was worried about the occurrence of loss learning during the Covid 19 pandemic. The purpose of this study was to examine qualitatively descriptively about the implementation of literacy and numeracy learning in the students of SD Negeri 16 Siantan, North Pontianak, as one of the selected driving schools in the province of West Kalimantan. This research method is qualitative, by collecting primary data generated from field observations (schools), interviews with several related parties such as school principals, classroom teachers, students, and campus ambassadors teaching 3 (KM 3) and supported by data secondary data obtained from references or literature relevant to the research topic. Based on the research activities carried out, it can be concluded that the implementation of driving curriculum-based learning related to literacy and numeracy skills has been carried out well even though it requires adjustments to room conditions and the limited supporting facilities available. The number of students in the study group and the learning support model tools determine the effectiveness of learning with an independent curriculum.